Price escalation of unit rate for construction works of brick wall and boundary wall of NS Construction due to unusual increase of construction material price - Brac University (Brac University, 2023)
This record consists of general correspondence regarding the request for price escalation of unit rate for construction works of brick wall and boundary wall of NS Construction due to unusual increase of construction material price for BRACU new campus project.